Manajemen Kesehatan Terpadu: Tinjauan Literatur tentang Pendekatan Efektif untuk Layanan Kesehatan yang Berkualitas dan Berkelanjutan - Robby Prayuda; Eka Fauzihardani; Yulhendri Yulhendri; Rino Rino; Sari Mustika; Ranggi Rahimul Insan; Fahmil Haris (Postgraduate, University of Mataram, 2024)
Health is a fundamental aspect of human life, and providing quality and sustainable healthcare remains a significant challenge globally. With the advancement of medical technology and health information systems, delivering effective, efficient, and affordable healthcare has become increasingly complex. In this context, Integrated Health Management (IHM) has emerged as a promising approach to improving healthcare quality and sustainability. IHM integrates various elements of the healthcare system, such as hospitals, clinics, healthcare professionals, and policies, to achieve more efficient and sustainable health outcomes. This approach aims to address fragmentation in healthcare services, where patients often receive disconnected care without coordination among specialists, medical staff, and institutions. This study conducts a systematic literature review to explore the impact of IHM on healthcare quality and sustainability. Data was gathered from three major academic databases: Scopus, ScienceDirect, and Google Scholar, using keywords such as